Root-associated bacterial endophytes from Ralstonia solanacearum resistant and susceptible tomato cultivars and their pathogen antagonistic effects - Upreti, Reshmi; Thomas, Pious (Frontiers in Microbiology, 2015)
This study was undertaken to assess if the root-associated native bacterial endophytes in tomato have any bearing in governing the host resistance to the wilt pathogen Ralstonia solanacearum. Internal colonization of roots by bacterial endophytes was confirmed through confocal imaging after SYTO-9 staining. Endophytes were isolated from surface-sterilized roots of 4-week old seedlings of known wilt resistant (R) tomato cultivar Arka Abha and susceptible (S) cv. Arka Vikas on nutrient agar after plating the tissue homogenate. Arka Abha displayed more diversity with nine distinct organisms while Arka Vikas showed five species with two common organisms (Pseudomonas oleovorans and Agrobacterium tumefaciens). Screening for general indicators of biocontrol potential showed more isolates from Arka Abha positive for siderophore, HCN and antibiotic biosynthesis than from Arka Vikas. Direct challenge against the pathogen indicated strong antagonism by three Arka Abha isolates (P. oleovorans, Pantoea ananatis and Enterobacter cloacae) and moderate activity by three others, while just one isolate from Arka Vikas (P. oleovorans) showed strong antagonism. Validation for the presence of bacterial endophytes on three R cultivars (Arka Alok, Arka Ananya, Arka Samrat) showed 8-9 antagonistic bacteria in them in comparison with four species in the three S cultivars (Arka Ashish, Arka Meghali, Arka Saurabhav). Altogether 34 isolates belonging to five classes, 16 genera and 27 species with 23 of them exhibiting pathogen antagonism were isolated from the four R cultivars against 17 isolates under three classes, seven genera and 13 species from the four S cultivars with eight isolates displaying antagonistic effects. The prevalence of higher endophytic bacterial diversity and more antagonistic organisms associated with the seedling roots of resistant cultivars over susceptible genotypes suggest a possible role by the root-associated endophytes in natural defense against the pathogen.